2016
DOI: 10.1002/stem.2466
|View full text |Cite
|
Sign up to set email alerts
|

Same-Single-Cell Analysis of Pacemaker-Specific Markers in Human Induced Pluripotent Stem Cell-Derived Cardiomyocyte Subtypes Classified by Electrophysiology

Abstract: Insights into the expression of pacemaker-specific markers in human induced pluripotent stem cell (hiPSC)-derived cardiomyocyte subtypes can facilitate the enrichment and track differentiation and maturation of hiPSC-derived pacemaker-like cardiomyocytes. To date, no study has directly assessed gene expression in each pacemaker-, atria-, and ventricular-like cardiomyocyte subtype derived from hiPSCs since currently the subtypes of these immature cardiomyocytes can only be identified by action potential profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 30 publications
(46 reference statements)
6
40
0
Order By: Relevance
“…Although traditionally hPSC-CMs are classified into the atrial-, nodal-, and ventricular-like subtypes, recent studies demonstrated that hPSC-CMs do not cleanly separate into these classes, and their properties represent a continuum, changing over time [2,38]. Our data supports this conclusion and enables observation of their development over time.…”
Section: Discussionsupporting
confidence: 80%
“…Although traditionally hPSC-CMs are classified into the atrial-, nodal-, and ventricular-like subtypes, recent studies demonstrated that hPSC-CMs do not cleanly separate into these classes, and their properties represent a continuum, changing over time [2,38]. Our data supports this conclusion and enables observation of their development over time.…”
Section: Discussionsupporting
confidence: 80%
“…The subtype of each hiPSC‐CMs was first determined by its AP profile through the clustering analysis, an established alternative method to patch clamp for subtype classification . The AP of a ventricular‐like cell shows a more prominent plateau phase than that of an atrial‐like and pacemaker‐like cell (Figure A1‐A3).…”
Section: Resultsmentioning
confidence: 99%
“…Current hiPSC‐CMs differentiation protocols typically yield ~70% CMs with ~15% of the CMs being the pacemaking subtype . Achieving higher‐purity populations is challenging because there is no established purification method, largely due to the lack of a reliable marker that can be used to sort cells by phenotype, maturity, or subtype.…”
Section: Introductionmentioning
confidence: 99%
“…3) (Bett et al 2013; Burridge D r a f t Lian et al 2012;Ma et al 2011;N. Sun et al 2012;Yechikov et al 2016), although ventricular-like hiPSC-CMs usually predominate (Burridge et al 2014;Lian et al 2012;Yechikov et al 2016). Specific cardiac cells subtype diversity has also been reported to evolve throughout the differentiation process.…”
Section: Previous Differentiation Techniquesmentioning
confidence: 99%
“…Specific cardiac cells subtype diversity has also been reported to evolve throughout the differentiation process. The ratio of nodal-, atrial-, and ventricular-like cells appears to be balanced during early differentiation, while ventricular-like cells predominate in older cell cultures (Burridge et al 2014;Lian et al 2012;Yechikov et al 2016). It is important to note that there is no consensus regarding the classification of hiPSC-CMs into subtypes.…”
Section: Previous Differentiation Techniquesmentioning
confidence: 99%